U-Model Based Adaptive Control of Gas Process Plant - Hasan, E. (Elsevier B.V., 2017)
Industrial process control holds great importance while dealing with nonlinear control. System modeling and controller design is considered to be a critical challenge for researchers as well as plant operators. Resultantly, significant amount of research work has been prompted in the area of Adaptive Control. Their biggest advantage is that unknown system parameters are tuned online and adjusted adaptively. In this research work, an adaptive controller, based upon a recently developed U-Model is suggested. U-Model is a simplified polynomial structure that adaptively adjusts system parameters online. Being less complex in structure, design and development of U-Model based controller is simple. Previously, it has performed well in different applications regarding system identification and controller design. This motivates us to undertake a Gas Process Plant for our research work using U-Model. The proposed control strategy is verified by a simulation. © 2017 The Authors.